If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 = 70 + -5x Reorder the terms: 7 + 4x = 70 + -5x Solving 7 + 4x = 70 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 7 + 4x + 5x = 70 + -5x + 5x Combine like terms: 4x + 5x = 9x 7 + 9x = 70 + -5x + 5x Combine like terms: -5x + 5x = 0 7 + 9x = 70 + 0 7 + 9x = 70 Add '-7' to each side of the equation. 7 + -7 + 9x = 70 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 70 + -7 9x = 70 + -7 Combine like terms: 70 + -7 = 63 9x = 63 Divide each side by '9'. x = 7 Simplifying x = 7
| 5x+6=-120-92 | | 4m-1=19 | | 90x^2-71x-9=0 | | 5n^2+28n+15=0 | | 3x+4(x-5)=9x-18 | | 5(n+2)=45 | | 5+10n=51 | | -26-4=9-9x | | 5n-4=7 | | 12p^2-36p+24=0 | | 4x-81=7x | | x+2+x+2+x+x=24 | | t+4t=10-t | | 4x+5y=24 | | 2m-3-3m=-27 | | x^2-6x-391=0 | | x^2+y^2=196 | | 14p^2+140p=126 | | x+2+x=344 | | x^2+3x=-42 | | 3x+5y=36 | | 4x-3=12x-18 | | 2x+6(x-1)=7x+5 | | f(-1)=4x^2-x-3 | | 2x=8-8 | | 5x+38=12x-8 | | 6-9x=36-30x | | 56c^2+19cd-15d^2= | | x-1+x+2+x=37 | | 4(y+2)+3(y+6)=-12 | | -3x+6=4 | | 45x=90 |